Lipid profile in patients of preeclampsia: A comparative study (Panacea Journal of Medical Sciences, 2016)
Preeclampsia occurs in 7 to 10% of pregnancies worldwide. At present most popular theory is an oxidative stress. Abnormal lipid profiles and species may have a role in promotion of oxidative stress and vascular dysfunction seen in pre-eclampsia. The study was carried out to evaluate lipid profile in subjects with preeclampsia and to compare lipid profile in subjects of preeclampsia as compared to normal pregnant women from 26 weeks of gestation till term. Pregnant women with and without preeclampsia between 26weeks-till term were compared for serum total cholesterol, triglycerides(TG), low density lipoprotein(LDL), high density lipoprotein (HDL) and very low density lipoproteins(VLDL). The study was conducted in tertiary care hospital over a period of one year. The total serum cholesterol, triglycerides, LDL and VLDL was significantly raised in subjects with preeclampsia as compare to pregnant women without preeclampsia. Considering the results in this study correlating with the various other studies, it can be concluded that dyslipidemia is significantly evident in preeclampsia and plays an important role in its pathogenesis. The preventive measures taken to avoid dyslipidemia like dietary control, weight reduction and physical activity and its positive effect on pregnancy needs to be further studied.